1997
DOI: 10.1172/jci119647
|View full text |Cite
|
Sign up to set email alerts
|

Intercellular adhesion molecule-1 deficiency prolongs survival and protects against the development of pulmonary inflammation during murine lupus.

Abstract: One of the characteristic features of the lupus syndrome in humans and mice is the organ-specific accumulation of leukocytes within a variety of different tissues; however, the etiology of this phenomenon remains unclear. The work presented here determined the role of intercellular adhesion molecule (ICAM)-1 in the development of pulmonary leukocyte accumulation by generating MRL/MpJ-Fas lpr mice that are genetically deficient in this critical adhesion molecule. Interestingly, these MRL/MpJ-Fas lpr ICAM-1 knoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 34 publications
1
33
0
Order By: Relevance
“…For example, ICAM-1 neutralizing antibody blocks cell-associated human immunodeficiency virus type 1 transmission across a cervical epithelial monolayer (4). Modulating ICAM-1 signaling may also alleviate the outcomes of many diseases, such as colonic inflammation, asthma, and polymicrobial sepsis (1,11,12,19,23,31). Our current findings support an important role of ICAM-1 in WNV neuroinvasion and also suggest the potential application of modulating ICAM-1 signaling in controlling the pathogenesis of West Nile encephalitis and other neuroinvasive flaviviral infections.…”
supporting
confidence: 73%
“…For example, ICAM-1 neutralizing antibody blocks cell-associated human immunodeficiency virus type 1 transmission across a cervical epithelial monolayer (4). Modulating ICAM-1 signaling may also alleviate the outcomes of many diseases, such as colonic inflammation, asthma, and polymicrobial sepsis (1,11,12,19,23,31). Our current findings support an important role of ICAM-1 in WNV neuroinvasion and also suggest the potential application of modulating ICAM-1 signaling in controlling the pathogenesis of West Nile encephalitis and other neuroinvasive flaviviral infections.…”
supporting
confidence: 73%
“…Our careful analyses of renal function (BUN and albuminuria) allow us to state with assuredness that none of the ten complement-inhibited animals that died spontaneously did so from renal disease. Clearly there are other organ systems involved in lupus mice (20,30), as is true in the human disease.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, this conclusion came into question from studies by Lloyd et al (36) with MRL/lpr mice with targeted deficiency of ICAM-1. Their results suggested that pulmonary disease led to mortality in MRL/lpr mice; this was delayed in ICAM-1-deficient animals.…”
Section: Discussionmentioning
confidence: 99%